Calculation of the Probability of Landslides Caused by Precipitation Applying the Janbu and MonteCarlo Method in Skarn-Type Mineral Deposits - Castañeda, Carlos (2021)
In this research, we will focus on analyzing the influence of the rains on mining companies in the district of San Marcos in the department of Ancash, Peru. To do in this investigation, a stability analysis of slopes with limit equilibrium methods, being the Janbú the one selected for said study. On the other hand, it calculated the probability of failure of the slopes using methods probabilistic such as Monte Carlo. Such studies mentioned were applied with the help of the Slide software.